The Effect of Free Shipping Promotion and Customer Trust on Shopee Customer Loyalty of Students of Management Study Program, Tribhuwana Tunggadewi University, Malang - Darius Anugrah; Cakti Indra Gunawan; Fendiyatmi Kusufa (International Research & Development for Human Beings (IRDH), 2026)
The development of digital technology is driving the growth of e-commerce in Indonesia, including Shopee, which has become a popular online shopping platform among students. Increasingly fierce competition between e-commerce platforms requires companies to implement effective marketing strategies to attract and retain customers. This study aims to analyze the effect of free shipping promotions and customer trust on Shopee customer loyalty among students. The research method used is a quantitative approach with data collection techniques through distributing questionnaires to student respondents. Data analysis was conducted using multiple linear regression tests to determine the effect of each independent variable on the dependent variable. The results show that free shipping promotions and customer trust have a positive and significant effect on customer loyalty, both partially and simultaneously. Customer trust is the variable that has the most dominant influence in increasing loyalty. These findings indicate that appropriate promotional strategies and increasing customer trust are crucial in maintaining customer loyalty on e-commerce platforms.